Criminología de la personalidad antisocial: Asociación entre la conducta pandilleril y la conducta disocial en adolescentes - Granados Muñoz, Rolando (Archivos de criminología, seguridad privada y criminalística, 2020)
The gang is linked to public health problems and is associated with different types of behavior. According to gang theory, there are multiple factors that influence its development. This investigation with the purpose of identifying the association between gang behavior and dissocial behavior, a survey was applied to 152 adolescents, 9% indicating being gang members in an age range of 13 to 18 years, operationalization is made through the Gang Behavior Scale and the Dissocial Behavior Scale (ECODI27). Statistical comparative analyzes were made using the student's t-test, Pearson's product-moment correlation coefficient and multiple linear regression. Among the results, the two types of behavior refer to men, those who claim to be part of a gang, those who have tattoos and those who practice graffiti; a correlation of r=.754 was obtained between gang behavior and dissocial behavior, the predictors of gang behavior are graffiti, lawsuits and weapons and school dropout. These represent important findings to raise awareness of the study needs of gang members and their effective intervention.